2017
DOI: 10.1038/ncomms14778
|View full text |Cite|
|
Sign up to set email alerts
|

Superfast assembly and synthesis of gold nanostructures using nanosecond low-temperature compression via magnetic pulsed power

Abstract: Gold nanostructured materials exhibit important size- and shape-dependent properties that enable a wide variety of applications in photocatalysis, nanoelectronics and phototherapy. Here we show the use of superfast dynamic compression to synthesize extended gold nanostructures, such as nanorods, nanowires and nanosheets, with nanosecond coalescence times. Using a pulsed power generator, we ramp compress spherical gold nanoparticle arrays to pressures of tens of GPa, demonstrating pressure-driven assembly beyon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 35 publications
1
41
0
Order By: Relevance
“…However, due to the isotropic nature of the spherical Au NPs, they possess random orientations (amorphous nature) in the superlattice films and final superstructures, as shown in Figure c, and Figures S10 and S11 in the Supporting Information. This phenomenon is similar to that observed in high pressure–induced sintering of Au NP arrays …”
supporting
confidence: 86%
“…However, due to the isotropic nature of the spherical Au NPs, they possess random orientations (amorphous nature) in the superlattice films and final superstructures, as shown in Figure c, and Figures S10 and S11 in the Supporting Information. This phenomenon is similar to that observed in high pressure–induced sintering of Au NP arrays …”
supporting
confidence: 86%
“…XRD was collected while the nanocrystals were loaded up to 7.5 GPa and as pressure was released. The pressure was limited to 7.5 GPa to avoid sintering between the nanocrystals, which has been observed by our group and others at higher pressures (17)(18)(19). The XRD peak position and width (full width at half max) were observed to change with increasing and decreasing pressure and quantified at each pressure (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…16). There have been some interesting studies that show new nanostructures, such as gold or CdSe nanowires can be synthesized by compression of their small nanoparticles [32][33][34] . In this work, we found that large area of compact and fused morphology changes appears in nanosheet assemblies upon mechanical compression.…”
Section: Resultsmentioning
confidence: 99%